The anatomy of a crisis: investment and output in Britain 1958-62 - WILLIAMS, D. (PSL Quarterly Review, 2014)
Although the determination of the trend, not the cycle, of economic growth is now the fashion, a conjunction of economic phenomena which resemble a distinguishable part of a trade cycle has recently been witnessed. The present article is concerned with the period 1959-61, and the changing patterns in investment and growth which may have important implications for the future trend of economic growth in Britain. It is argued that a high investment economy in a free enterprise society tends to be more unstable than a high consumption economy. If the 1959-61 boom marks Britain’s re-emergence as a high investment economy it will become a more volatile one. The chief problem considered is whether or not England is entering the first downswing of the post-war trade cycle as a result of these changes in investment and consumption. JEL: E20, E32, F32, F44, O40